Glicerina bruta em substituição ao milho na alimentação de caprinos e ovinos - MENDES, Giorgio Oliveira (2019)
The objective of this study was to evaluate the effects of inclusion of goat and sheep crude glycerin in feedlot on intake and apparent digestibility of dry matter (DM) and its components; ingestive behavior; metabolic profile; hydrogen potential (pH); ammonia nitrogen (NNH³); volatile fatty acids (VFAs). Were used 04 goats and 04 sheep without defined racial pattern, castrated, age and initial body weight (57 kg ± 6.34 Kg), rumen fistulated and cannulated, confined in individual stalls and distributed in four treatments in a design. double Latin square 4 x 4, with four experimental periods, each lasting 21 days, with 14 days of adaptation to the treatments and 7 days of collection. Experimentais diets were formulated to be isonitrogenous and isoenergetic and named: Level G0 - control without added crude glycerin in the diet dry matter, Level G5 - 5% crude glycerin in the diet dry matter, Level G10 - 10% glycerin dietary dry matter and Level G15 - 15% of crude glycerin in the diet dry matter. The diets were additionally composed of soybean meal, corn, urea and ammonium sulfate (9: 1 ratio), common salt and mineral mixture, Tifton 85 grass hay with a roughage: concentrate ratio of 50:50, fed twice a day. (8:00 e 16:00). There was a linear effect (P <0.05) for the intake of DM, CP, OM, EE, NDF, CHT, CNF and NDT. There was a linear effect (P <0.05) on the digestibilities of DM, OM, NDF, CHT and NDT. The ingestive behavior of rumination time (TRUM) There was a linear effect (P <0.05), while the efficiencies in hours were influenced by the inclusion of crude glycerin in the diet (P <0.05) in feeding efficiency (g MS / h) (EAL), feed efficiency (g NDF / h), rumination efficiency (g MS / h) (ERU), rumination efficiency (g NDF / h). As for blood metabolites there was a linear increasing effect (P <0.05) on serum urea concentration, phosphorus, aspartate amino transferase, cholesterol, triglycerides and a linear decreasing effect (P <0.05) on serum uric acid concentration. magnesium (mg / dL), and quadratic effect on serum albumin concentration. For ruminal parameters there was a linear decreasing and quadratic effect (P> 0.05) for time on hydrogen potential (pH) and time on treatment. N-NH³ concentrations had a linear decreasing effect (P <0.05) on time and treatment. Concentrations of short chain fatty acids where acetic acid had linear decreasing effect on treatment and quadratic effect on time (P> 0.05). Propionic acid showed increasing linear effect on treatment and time and quadratic effect on time and treatment (P <0.05) with maximum point at level 14.94 and hour 5.04. There was influence for butyric acid on time, treatment * time and quadratic time influence with saddle point at level 5.4 and hour 3.75. Crude glycerin can be included in up to 10% of the goat and sheep diet because it does not compromise the functioning of animal metabolism at satisfactory levels.